Investigating the influence of augmented reality marketing application on consumer purchase intentions: A study in the E-commerce sector - Thi Thuy An Ngo; Thanh Tu Tran; Gia Khuong An; Phuong Thy Nguyen (Computers in Human Behavior Reports)
The rapid digitalization of e-commerce demands innovative solutions to enhance consumer engagement and address the sensory limitations of online shopping. Augmented Reality (AR) technology offers potential remedies by integrating virtual elements into real-world environments, enriching user experiences with interactive and immersive features. This study explores the impact of AR marketing applications on consumer purchase intentions in the e-commerce sector. Using a quantitative approach, data were collected from 315 participants with experience using AR in e-commerce contexts through a 5-point Likert scale questionnaire. The study employed Partial Least Squares Structural Equation Modeling (PLS-SEM) technique to analyze the relationships between AR characteristics (interactivity, vividness, novelty, and informativeness), consumer perceptions (perceived enjoyment, usefulness, and hedonic value), and outcomes (satisfaction, attitude, and purchase intentions). The findings indicate that AR features significantly influence consumer perceptions and experiences, with vividness and informativeness emerging as particularly impactful factors. Interestingly, while interactivity enhanced user engagement, it showed no significant impact on perceived usefulness. The study also revealed that perceived enjoyment and hedonic value significantly influenced consumer satisfaction and attitudes towards AR-enhanced e-commerce platforms, whereas the relationship between perceived usefulness and satisfaction was not supported. The results also confirmed the positive relationship of satisfaction and attitude on behavior intention. These findings provide valuable insights for e-commerce businesses and AR developers, highlighting the need to balance utility with engaging experiences in AR application design. The research contributes to the understanding of AR's efficacy as a marketing tool in e-commerce for future research in this rapidly evolving field.